The role of knowledge sharing and creative self-efficacy on the self-leadership and innovative work behavior relationship - Hira Salah ud din Khan; Peihuan Li; Muhammad Salman Chughtai; Muhammad Tahir Mushtaq; Xingzhu Zeng (Journal of Innovation & Knowledge (JIK), 2023)
The current study employs social cognitive theory to analyze the moderated mediation model of self-leadership and innovative work behavior. Further, this research assesses the mediating impact of knowledge sharing, and the moderating effect of creative self-efficacy in the above-mentioned direct relationship. To test this model, data were gathered, at two different times, from 283 subordinates and 129 supervisors, working in various software companies in major cities in Punjab, Pakistan. The findings showed a significant impact of self-leadership and innovative work behavior. Additionally, the results supported the mediating role of creative self-efficacy in the association between these two qualities. Moreover, a higher level of knowledge sharing strengthens the link between self-leadership and innovative work behavior. The study revealed that self-leadership is vital in fostering innovative work behavior. This research recommends how businesses might use self-leadership strategies to promote innovative work behavior.
Keywords: M10; M12; O32; D23; J29; 030; 650; Self-leadership; Creative self-efficacy; Knowledge sharing; Innovative work behavior